On the 1H NMR spectra of weak electrolytes under the influence of strong electrolytes at low concentrations - Madeira, Pedro P. (2023)
Physical chemistry has yet to provide a convincing explanation for the many distinct ways the cosolute's properties are perturbed when under the field of action of salt ions. For that reason, a systematic and gradual approach to the problem was sought, with the present work being a step in that direction. Thus, acetic acid and n-butylamine were selected as simple models for the charged carboxyl and amine groups in more complex solutes, like proteins. The influence of the gradual addition of inorganic salts on these compounds' proton nuclear magnetic resonance spectra was analyzed. The salt concentration varied from 0.01 to roughly 100 mmol.L−1. The reported results suggest that at a low salt concentration (<c.a. 10 mmol.L−1), the effect on the properties of the weak electrolyte results from an indirect action of the salt ions. More specifically, strong electrolytes perturb the auto-dissociation of water whereby H+ or OH– ions are released. Some salts, like NaCl, releasing H+, suppress the dissociation of acetic acid and are neutral to n-butylamine. Other salts, like NaSCN, releasing OH–, shift the reaction of n-butylamine with water towards the reverse direction and are neutral to acetic acid. Moreover, the required quantity of added salt to promote the effects under consideration depends, to a considerable extent, on the valency of the salt ion, the decreasing order of efficacy being as follows: trivalent > divalent > monovalent. Therefore, the experimental facts herein reported show that the effect of salt ions at low concentrations upon the properties of other solutes can be rationalized by conventional chemical concepts, in which chemical equilibrium plays an important role. Furthermore, the results strongly support the classical interpretation of salt ions, which are charged bodies that, in solution, exert chiefly electrostatic forces.